Photocatalytic hydrogenation by g-C3N4 based semiconductor nanomaterials - Goh, Zoey Jie Yi (Nanyang Technological University, 2020)
Increased environmental awareness has highlighted the need to search for more renewable sources of energy production. Organic synthesis, primarily through the method of hydrogenation, has been managed to achieve for valuable chemicals by renewable resources [1]. However, this method is carried out through thermal catalysis and relies on the use of hydrogen (H2) [2]. Intents to counterbalance the environmental and volatilization implications of H2 gas. Assessing the acquisition of organic synthesis through photocatalytic hydrogenation has been sought as a feasible method to help resolve global environmental issues [3, 4]. Ru/g- C3N4 nanocomposite is one of the possible organic semiconductor substrates for selective reactivity in the processing of bioactive alcohols, aldehydes and ketones [5]. However, there is a lack of studies to achieve photocatalytic hydrogenation using Ru/g-C3N4. This research thus focuses on the further production of organic synthesis using the hydrogen transfers reaction of the Carbonyl (C=O) functional groups. Apart from the importance of the reduction of C=O bonds, the hydrogen transfers reaction of the Alkene (C=C) functional groups will also be discussed for comparison. Nevertheless, these reactions will be performed with the photocatalysts Ru/g-C3N4 and Pt/g-C3N4, where Pt acts as a comparative co-catalyst. The photocatalysts characteristics in terms of chemical composition, structural composition and optical properties will be analysed. Furthermore, photocatalytic reactions with different reagents will be performed. The results will be analysed in terms of H2 evolution and hydrogenation, as both results should be pre-requisites and countervailing. In conclusion, the experimental results obtained have shown that the photocatalysts Ru/g-C3N4 and Pt/g-C3N4 are potential for photocatalytic hydrogenation reactions. Respective the reagents have a favourite photocatalysts, the findings show the preferential reactivity performance of the different photocatalysts.